PLURALISME MORAL DALAM PENDIDIKAN HUMANISTIK DI ERA SOCIETY 5.0 - Nur Rokhmatulloh (Journal Multicultural of Islamic Education, 2022)
Human Values ​​consisting of Truth, Virtue, Peace, Compassion and Nonviolence are values ​​that are relevant to the values ​​of the character of the nation. These values ​​are the fruit of the principles of humanistic education (Freedom, Equality and Brotherhood) because they are universal, therefore these values ​​must be prioritized and can be developed in the moral formation of students, so that the role of educators does not only focus on the transfer of knowledge, however, educators must emphasize more on moral values ​​/ transfer of values ​​which cannot be replaced by any sophisticated technology in this era of Society 5.0. Plurality can be defined as religion, nationality, political views, political jurisdiction, and individual opinion, all of which come together in a society. Therefore, talking about pluralism in society is talking about freedom and democracy which concerns human morals. Moral pluralism wants a form of cooperation in morals. One religion may compromise with other religions in an effort to achieve the same goals and objectives. In the sense of looking for a meeting point of religions, although exoterically, religion is plural (religious pluralism), but esoterically, it all leads to "One God or God Almighty.